Antigonos of Karystos and Polemon of Ilion: The Pergamene Contribution to the Theory and History of Greek Art - Polański, Tomasz (Folia Orientalia, 2026)
I am going to collect dispersed items of information which clearly refer or seem to be suggestive of the Aeolic, Pergamene or Attalid school of art historians which developed in the first half of the 2nd century BC and discuss their idiosyncratic methods and original contribution to the Greek intellectual life of the Hellenistic period. Even the fragmentary history of the Attalid art collections which can be reconstructed from the archaeological data and the scarce information in the literary sources shows that the collections grew as a result of various factors: 1. wartime robbery. 2. purchases of artworks. 3. a well‑thought out programme of reproducing original Greek artworks. The Attalids must have had professional art historians at their side as consultants. We can identify two of them by name: Antigonus of Karystos and Polemon of Ilion. A number of passages testify to a lively academic debate between them. In the course of their professional polemics they discussed the problems of authorship and authenticity of artworks, they adduced biographical details in their efforts to establish the personal identities of the artists and paid tribute to their heroes with colourful anecdotes. They attributed artworks to alternative authors. They also constructed complicated genealogical trees of schools of painting and sculpture, along the principle of master/pupil relations. Their epigraphic studies must have been inspired and influenced by the editors of the Aeolic Archaic poets.